2002
DOI: 10.1046/j.1524-4741.2002.08613.x
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Plasmacytoma of the Breast: A Case Report

Abstract: Plasmacytoma of the breast is a rare condition that may occur as a solitary finding or in association with multiple myeloma. Of the cases of plasmacytoma of the breast that have been described, nearly half have been bilateral. We report a case of bilateral plasmacytoma of the breast detected on a routine screening mammogram in a patient with a recent diagnosis of multiple myeloma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…Our patient was referred with bilateral breast masses. In an approach to a patient with bilateral breast masses, differential diagnosis includes: fibroadenomas, complex cysts, metastasis, lymphoma, synchronous breast cancer, focal fibrosis, fat necrosis, abscess, and phyllodes tumor [20]. Metastatic lesions of the breast from extramammary neoplasms are rare and in larger studies have been reported to constitute 0.4 to 2% of all breast malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…Our patient was referred with bilateral breast masses. In an approach to a patient with bilateral breast masses, differential diagnosis includes: fibroadenomas, complex cysts, metastasis, lymphoma, synchronous breast cancer, focal fibrosis, fat necrosis, abscess, and phyllodes tumor [20]. Metastatic lesions of the breast from extramammary neoplasms are rare and in larger studies have been reported to constitute 0.4 to 2% of all breast malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…It may occur as the initial presentation or in the setting of known multiple myeloma 42,43. In contrast with solitary plasmacytoma of the bone, extramedullary plasmacytoma is associated with symptomatic multiple myeloma in only 15% of patients 44…”
Section: Hematologic Diseasementioning
confidence: 99%
“…On US, the masses may be either welldefined or ill-defined. They are round and hypoechoic with posterior shadowing or enhancement (14,15). One patient with bilateral plasmacytoma is reported in this study.…”
Section: Plasmacytomamentioning
confidence: 66%
“…It may present as a solitary finding or in association with disseminated multiple myeloma (14,15). More than half of the lesions are unilateral, with the majority of the cases occurring in the setting of multiple myeloma (14,15). The mean age at presentation of breast plasmacytomas is 53 years.…”
Section: Plasmacytomamentioning
confidence: 99%